Explore methods to store energy for small-scale wind turbine - Zhuang, Xiaojing (2019)
Renewable energy attracts world’s attention to mitigate the world energy crisis. Renewable energy takes advantage of renewable source in nature which can be replenished naturally, such as rain, wind and sunlight. Among those renewable energy technologies, wind energy makes use of wind turbine to convert energy stored in the wind into electricity. However, due to the instability of wind feature and the changeful demand of electricity, a proper energy storage system is required to be installed with wind turbine to increase the wind utilization efficiency. This report is to explore methods to store energy for small-scale wind turbine. At first section, typical wind turbine structure was described, and small-scale wind turbine was defined. By understanding the small-scale wind turbine, suitable energy storage systems were selected. In addition, working principle and three main applications of those selected storage systems are reviewed and explained. After that, case study on Singapore energy background was discussed and a 20-years’ life cycle cost study was conducted on one small-scale wind turbine. The result for life cycle cost was expressed in terms of annual cost ($/year, $/kW-year and $/kWh-year).